Un acercamiento empírico a la función de producción de compost para 33 países - David Andrés Camargo Mayorga; Octavio Cardona García; Juan Manuel González Guzmán (Atlantic Review of Economics (ARoEc), 2018)
– The economic literature related to composting has a marked bias towards the inclusion of case analysis and cost-benefit analysis. Studies dedicated to a microeconomic analysis of compost production processes are few or nil. Some of the reasons that explain this gap in the literature range from the lack of economic theories that explain some environmental phenomena, to the lack of data related to composting. The objective of this article is to propose a function of compost production using econometric methods for 33 countries in the period 2011-2016. Through a system of equations, a linearized Cobb-Douglas type production function is constructed that serves as an approximation of the behavior and yields of this product for agricultural use. The most significant conclusion is that the returns to capital and agricultural labor were decreasing to scale.
Keywords: D24; Q15; Q56; 330; Compost; Production function; Solid waste